Deciphering thrust fault nucleation and propagation and the importance of footwall synclines. (April 2016) - Ferrill, David A.; Morris, Alan P.; Wigginton, Sarah S.; Smart, Kevin J.; McGinnis, Ronald N.; Lehrmann, Daniel
Abstract: In this paper, we analyze small scale examples of thrust faults and related folding in outcrops of the Cretaceous Boquillas Formation within Big Bend National Park in west Texas to develop detailed understanding of the fault nucleation and propagation that may aid in the interpretation of larger thrust system structure. Thrust faults in the outcrop have maximum displacements ranging from 0.5 cm to 9 cm within competent limestone beds, and these displacements diminish both upward into anticlines and downward into synclines within the interbedded and weaker mudrock layers. We interpret the faults as having nucleated within the competent units and partially propagated into the less competent units without developing floor or roof thrusts. Faults that continued to propagate resulted in hanging wall anticlines above upwardly propagating fault tips, and footwall synclines beneath downwardly propagating fault tips. The observed structural style may provide insights in the nucleation of faults at the formation scale and the structural development at the mountain-range scale. Décollement or detachment layers may be a consequence rather than cause of thrust ramps through competent units and could be over interpreted from seismic data. Highlights: Thirty-four small thrust faults provide analogs for larger cross-section or seismic-scale thrusts. Thrust fault system formed without developing floor or roof thrusts. Max. displacements are in limestone beds where they nucleated and tip into mudrock. Displacements diminish up into hanging wall anticlines and down into footwall synclines. Décollement layers may be a consequence rather than cause of thrust ramps.